2019
DOI: 10.1002/bse.2287
|View full text |Cite
|
Sign up to set email alerts
|

Ambidextrous culture, contextual ambidexterity and new product innovations: The role of organizational slack and environmental factors

Abstract: Contextual ambidexterity, defined as the simultaneous pursuit of alignment and adaptability at business unit, is linked to several organizational outcomes including improved performance and innovation outcomes. Extant research posits ambidextrous organizational culture as an important enabler to contextual ambidexterity but suffers from a lack of a well‐meaning scale for the same. In addition, there is very little understanding as to how tasking and facilitating environment can be on firms' endeavour for conte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
79
0
5

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(86 citation statements)
references
References 69 publications
2
79
0
5
Order By: Relevance
“…Recent studies [17,18] suggested that key ingredients for contextual ambidexterity are pursuance of decentralization and continual innovation. The organizational ambidexterity is the capability on part of the firm to perform not only on incremental quality progresses but also radical innovative developments that explore new avenues and opportunities.…”
Section: Contextual Ambidexterity and New Product Innovation Outcomesmentioning
confidence: 99%
“…Recent studies [17,18] suggested that key ingredients for contextual ambidexterity are pursuance of decentralization and continual innovation. The organizational ambidexterity is the capability on part of the firm to perform not only on incremental quality progresses but also radical innovative developments that explore new avenues and opportunities.…”
Section: Contextual Ambidexterity and New Product Innovation Outcomesmentioning
confidence: 99%
“…With the internal dynamics and external competition from low level to high level, environmental changes will optimize the organizational results and push forward the organizational resources [53]. In other words, on one hand, the high level ambidexterity environment makes some products, processes and administration obsolete and require new ones to be developed [54]. In this case, the surrounding resources (such as knowledge) will be mobilized to promote product and technology innovation through organizational learning and exploring new markets and technologies, to strengthen the knowledge absorptive capacity, to minimize the threat of resource, to increase strategic certainty, to plan accuracy and skill exploration [25][26][27], then to form gain-spiral of organizational resources and to meet organizational needs of intellectual resources [55].…”
Section: Plos Onementioning
confidence: 99%
“…We adapted construct scale from previous literature and changed the word and sentence to improve the understanding of Chinese informants [6,17,24,36,69]. We apply the seven-point Likert-type scale to measure these items with endpoints of "strongly disagree" and "strongly agree."…”
Section: Methodsmentioning
confidence: 99%
“…We measure product innovation by utilizing five items to following the previous literature [ 7 , 69 ]. The respondents are required to answer the questions and evaluate the extent to which their firms are successful compared to their major competitors in terms of (1) quickly launching new products into the market, (2) applying advanced production facilities, (3) having a better market response in product modifications and innovations, (4) having state-of-the-art technology in products, (5) being more successful with their product innovations.…”
Section: Methods and Datamentioning
confidence: 99%